Muslihat Yakub dalam Mendapatkan Hak Kesulungan Dari Esau - Siprianus Leu, Kornelius (Fakultas Teologi, Universitas Sanata Dharma, 2024)
The lives of Jacob and Esau, Isaac's twin sons, were filled with tension and competition. Genesis 25:23 tells how the competition between the two was even prophesied by God himself from the time they were conceived. The rivalry between the two continued in the event of Jacob taking away the blessing and birthright from Esau through